logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
0 votes

$ ^{\sim}(p \wedge q)$ is equivalent to

$\begin {array} {1 1} (A)\;(^{\sim}p)V q & \quad (B)\;(^{\sim}p)V (^{\sim}q) \\ (C)\;(^{\sim}p)\wedge (^{\sim}q) & \quad (D)\;(p) V (^{\sim}q) \end {array}$

Can you answer this question?
 
 

1 Answer

0 votes
p q $^{\sim}p$ $^{\sim}q$ $p \wedge q$ $ ^{\sim} (p \wedge q)$ $(^{\sim}p) v (^{\sim}q)$
T T F F T F F
T F F T F T T
F T T F F T T
F F T T F T T
Ans : (B)
So, $ ^{\sim}(p \wedge q)$ is equivalent to $(p) V (^{\sim}q)$

 

answered Jan 24, 2014 by thanvigandhi_1
edited Jan 24, 2014 by thanvigandhi_1
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...